A survey of energy efficiency optimization in heterogeneous cellular networks - Abdulkafi A.A.; Sileh I.K.; Chieng D.; Kiong T.S.; Ghaleb A. (Korean Society for Internet Information, 2023)
Heterogeneous networks; Mobile telecommunication systems; Network management; Surveys; Sustainable development; Wireless networks; Economic sustainability; Energy efficiency metrics; Energy efficiency optimizations; Heterogeneous cellular networks; Heterogeneous Network (HetNet); HetNet; Load adaptive; SLEEP mode; Energy efficiency